2017
DOI: 10.1021/acsami.7b08071
|View full text |Cite
|
Sign up to set email alerts
|

A Nonchlorinated Solvent-Processable Fluorinated Planar Conjugated Polymer for Flexible Field-Effect Transistors

Abstract: High carrier mobilities have recently been achieved in polymer field effect transistors (FETs). However, many of these polymer FET devices require the use of chlorinated solvents such as chloroform (CF), chlorobenzene (CB), and o-dichlorobenzene (DCB) during fabrication. The use of these solvents is highly restricted in industry because of health and environmental issues. Here, we report the synthesis of a low band gap (1.43 eV, 870 nm) semiconducting polymer (PDPP2DT-F2T2) having a planar geometry, which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The onsets of oxidation potential for PDPP2DT-F2T2, PDPPF2T2DPP-T2, PDPPF2T2DPP-TVT, and PDPPF2T2DPP-DTT were 0.49, 0.30, 0.28, and 0.33 V, corresponding to À5.38, À5.10, À5.08, and À5.13 eV of HOMO energy levels, respectively. Fluorine atoms in the PDPP2DT-F2T2 effectively lowered the HOMO level of the PDPP2DT-T2 polymer that has the same chemical structure except uorine atoms, 25 whereas electron-donating units (T2, TVT, and DTT moieties) slightly increased the HOMO levels compare to that of Scheme 1 Synthetic routes for the DPP-based regio-regular terpolymers. the PDPP2DT-F2T2 polymer.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The onsets of oxidation potential for PDPP2DT-F2T2, PDPPF2T2DPP-T2, PDPPF2T2DPP-TVT, and PDPPF2T2DPP-DTT were 0.49, 0.30, 0.28, and 0.33 V, corresponding to À5.38, À5.10, À5.08, and À5.13 eV of HOMO energy levels, respectively. Fluorine atoms in the PDPP2DT-F2T2 effectively lowered the HOMO level of the PDPP2DT-T2 polymer that has the same chemical structure except uorine atoms, 25 whereas electron-donating units (T2, TVT, and DTT moieties) slightly increased the HOMO levels compare to that of Scheme 1 Synthetic routes for the DPP-based regio-regular terpolymers. the PDPP2DT-F2T2 polymer.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
“…A comparison with PDPP2DT-T2 synthesized using DPP and 2,2 0 -bithiophene (T2) units revealed that the F2T2 donor moiety could facilitate a planar polymer backbone conformation and enhance crystallinity and carrier transport. 25 In this study, we synthesized three D 1 -A-D 2 -A-type DPPbased terpolymers, in which the D 1 unit was xed with the F2T2 donor, and D 2 units were varied using T2, (E)-1,2di(thiophen-2-yl)ethene (TVT), and dithieno[3,2-b:2 0 ,3 0 -d]thiophene (DTT). The variation of the second donor moiety enabled the ne-tuning of electronic structures, backbone conformation, and the resulting photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…24–26 In the above context, some DPP-based high mobility CPs processible with non-halogenated solvents, such as toluene, xylene, tetralin and tetrahydrofuran (THF), were also reported. 27–38 Lowering the regularity is generally adopted as an effective method to enhance the solubility of CPs. 27–29,39 For instance, Li et al reported toluene-processed DPP-based high mobility CPs with decreased regioregularity.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a great deal of research efforts have been devoted to phasing out halogenated solvents such as chloroform and chlorobenzene, which have been prevalent for optimizing the fabrication of lab‐scale OFET and PSC devices, because they are detrimental to both human health and the environment. In this context, a wide range of halogen‐free solvents including toluene, xylenes, and trimethylbenzenes have been recently proposed as greener solvent alternatives and some notable progress has been made . However, it remains in question whether those halogen‐free solvents, which are often claimed to be “green solvents,” are indeed practically applicable at an industrial‐scale for sustainable manufacturing of organic electronics due to the serious health hazards and harmful environmental impacts that they can pose (e.g., median lethal dose LD 50 for chlorobenzene: 1110 mg kg −1 , toluene: 5580 mg kg −1 , water: >90 000 mg kg −1 , and De minimis % limit allowed to release for chlorobenzene and toluene: 1.0%) .…”
Section: Introductionmentioning
confidence: 99%